Can digital education affect the educational setup? A narrative literature review of initiatives of digital education - Meetha Ram; Bakhtawar Nizamani (Journal of Digital Learning and Education, 2025)
Digital education refers to the integration of innovative technologies and digital tools in teaching and learning, often termed Technology Enhanced Learning (TEL) or e-learning. This narrative literature review critically examines how digital education initiatives have evolved in Pakistan and evaluates their contribution to transforming the country’s educational setup. Drawing on the European Framework for the Digital Competence of Educators: DigCompEdu, the study thematically reviews national and provincial programs, including Digital Pakistan, eLearn Punjab, and NGO-led initiatives, to identify progress, challenges, and policy implications. The review adopts a structured narrative approach using major academic databases (Scopus, ERIC, Google Scholar) and national reports published between 2010 and 2025. Findings highlight that while Pakistan has made notable progress in integrating ICT within education, disparities persist due to infrastructural limitations, policy inconsistency, and limited teacher digital competence. The paper argues that future initiatives should move beyond access-based interventions toward competence-oriented digital inclusion, teacher professionalization, and the localization of digital content. The study concludes by proposing a set of policy recommendations aligned with DigCompEdu’s six competence areas to guide sustainable digital transformation in Pakistan’s education system.